Complete genome sequence of the thermophilic Thermus sp. CCB_US3_UF1 from a hot spring in Malaysia. Issue 1 (December 2015) - Teh, Beng; Lau, Nyok-Sean; Ng, Fui; Abdul Rahman, Ahmad; Wan, Xuehua; Saito, Jennifer; Hou, Shaobin; Teh, Aik-Hong; Najimudin, Nazalan; Alam, Maqsudul
Abstract Thermus sp. strain CCB_US3_UF1 is a thermophilic bacterium of the genusThermus, a member of the familyThermaceae . Members of the genusThermus have been widely used as a biological model for structural biology studies and to understand the mechanism of microbial adaptation under thermal environments. Here, we present the complete genome sequence ofThermus sp. CCB_US3_UF1 isolated from a hot spring in Malaysia, which is the fifth member of the genusThermus with a completely sequenced and publicly available genome (Genbank date of release: December 2, 2011).Thermus sp. CCB_US3_UF1 has the third largest genome within the genus. The complete genome comprises of a chromosome of 2.26 Mb and a plasmid of 19.7 kb. The genome contains 2279 protein-coding and 54 RNA genes. In addition, its genome revealed potential pathways for the synthesis of secondary metabolites (isoprenoid) and pigments (carotenoid).